Pengembangan Modul Ajar Berbasis Etnomatematika pada Materi Bangun Datar untuk Peserta Didik Kelas V SD/MI - Azizah, Irsya; Karim, Karim; Suryaningsih, Yuni (FKIP Universitas Mataram, 2024)
Mathematics learning, especially on the concept of geometry, presents more examples or models of geometric shapes, both planes figure and solid figure that are less relevant to the students’ lives, this renders mathematical learning less meaningful. To provide meaningful mathematics learning, abstract learning should be assisted by media that concretizes the abstractness. One of the breakthroughs in learning mathematics for teachers is developing ethnomathematics-based mathematics learning. Teaching modules based on ethnomathematics are expected to be a means of increasing students' understanding of the material and introducing local culture. The purpose of this research is to produce teaching modules based on the Merdeka Curriculum on planes figure material for 5th grade students in elementary school that are valid, effective and practical. The research method used is development, namely Research and Development (R&D) using the Plomp development model which consists of the initial investigation phase, design phase, realization/construction phase, and test, evaluation and revision phase. Data analysis techniques used validation instruments, end-of-learning evaluation tests, and teacher and learner response questionnaires. Based on the results of the assessment of the validator obtained a value of 3.76 with a valid category. Based on the results of the final learning test that has been analyzed, the value is 88.89% with a very effective category. Based on the results of the teacher response questionnaire that has been analyzed, a value of 95.83% with a very practical category is obtained and the results of the student response questionnaire that has been analyzed are 87.19% with a very practical category. Thus, the teaching module based on the independent curriculum on plane figure material for fifth grade students can be declared valid, effective, and practical.